2022
DOI: 10.1161/jaha.121.024036
|View full text |Cite
|
Sign up to set email alerts
|

End‐Diastolic Forward Flow and Restrictive Physiology in Repaired Tetralogy of Fallot: A Systematic Review and Meta‐Analysis

Abstract: Background Pulmonary arterial end‐diastolic forward flow (EDFF) following repaired tetralogy of Fallot has been thought to represent right ventricular (RV) restrictive physiology, but is not fully understood. This systematic review and meta‐analysis sought to clarify its physiological and clinical correlates, and to define a framework for understanding EDFF and RV restrictive physiology. Methods and Results PubMed/MEDLINE, Embase, Scopus, and reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
(136 reference statements)
0
4
0
Order By: Relevance
“…Additionally, RV diastolic dysfunction was not measured in this study due to the complexity of RV geometry, filling, and tricuspid valve inflow. A recent meta-analysis demonstrated that other markers of RV diastolic dysfunction, including end-diastolic forward flow, may not be specific for restrictive RV physiology, demonstrating the complexity associated with CMR assessment of RV diastolic dysfunction [34]. Some studies suggest that more accurate assessments of RV diastology may be achieved with four-dimensional CMR [33].…”
Section: Limitationsmentioning
confidence: 99%
“…Additionally, RV diastolic dysfunction was not measured in this study due to the complexity of RV geometry, filling, and tricuspid valve inflow. A recent meta-analysis demonstrated that other markers of RV diastolic dysfunction, including end-diastolic forward flow, may not be specific for restrictive RV physiology, demonstrating the complexity associated with CMR assessment of RV diastolic dysfunction [34]. Some studies suggest that more accurate assessments of RV diastology may be achieved with four-dimensional CMR [33].…”
Section: Limitationsmentioning
confidence: 99%
“…The prevalence of EDFF among rTOF patients was 52, 43.3, and 49.5% at perioperative period, the first follow-up with a median time of 3 months and the last follow-up with a median time of 31 months, respectively. A recent systematic review and meta-analysis demostrated that the prevalence of EDFF among patients with repaired TOF was 46.5% (95% CI, 41.6–51.3%), which was closed to the result of our center ( 9 ). In our cohort, patients with PV dilatation had a lower incidence of EDFF than surgically corrected patients, and patients with TAP repair were more likely to appear EDFF after surgery.…”
Section: Discussionmentioning
confidence: 77%
“…End-diastolic forward flow (EDFF) in the main pulmonary artery, resulting from diastolic RV stiffness ( 4 ), is regarded as a manifestation of RV restrictive physiology in many studies ( 2 , 7 , 8 ). More and more attention has been paid to this phenomenon in rTOF patients ( 8 , 9 ), whereas the risk factors of EDFF are not clear, which mostly focus on preoperative physiological state and surgical procedures, such as transannular patch (TAP) ( 6 ). Studies of the association between TAP and EDFF have yielded divergent results.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with repaired TOF tend to require multiple PV replacements (PVR), and CMR plays a pivotal role in selecting the correct replacement timing [44,48,49].…”
Section: Cmr Findings In Tetralogy Of Fallotmentioning
confidence: 99%